Efficacy and Safety of Lenvatinib in Anaplastic Thyroid Carcinoma: A Meta-Analysis - Huang, Dongmei; Zhang, Jinming; Zheng, Xiangqian; Gao, Ming (Frontiers in Endocrinology, 2022)
Background When some targeted therapies have been tested to treat anaplastic thyroid carcinoma (ATC) both in preclinical and clinical studies, lenvatinib has shown some promising and potential efficacy. This study was to evaluate efficacy and safety of lenvatinib in patients with ATC. Methods The PubMed, the Cochrane Library, Embase, and ClinicalTrials.gov were searched for potential eligible studies from inception to February 1th, 2022. The outcomes included partial response (PR), stable disease (SD), disease control rate (DCR), median progression-free survival (mPFS), and median overall survival (mOS). Effect sizes for all pooled results were presented with 95 % CIs with upper and lower limit. Results Ten studies met the inclusion criteria. The aggregated results showed the pooled PR, SD, and DCR were 15.0 %, 42.0 %, and 63.0 %, respectively. And the pooled mPFS and mOS were 3.16 (2.18-5.60) months and 3.16 (2.17-5.64) months, respectively. Furthermore, PFS rate at 3 months (PFSR-3m), PFSR-6m, PFSR-9m, PFSR-12m, and PFSR-15m were 52.0%, 22.5%, 13.9%, 8.4%, and 2.5%, respectively. Meanwhile, the 3-month OS rate (OSR-3m), OSR-6m, OSR-9m, OSR-12m, and OSR-15m being 64.0%, 39.3%, 29.7%, 18.9%, and 14.2%, respectively. The most common adverse events (AEs) of lenvatinib were hypertension (56.6%), proteinuria (32.6%), fatigue (32%). Conclusions This meta-analysis showed lenvatinib has meaningful antitumor activity, but limited clinical efficacy in ATC.